Vulnerability and welfare: Findings from the fourth round of the Myanmar Household Welfare Survey (October to December 2022) - Myanmar Agriculture Policy Support Activity (International Food Policy Research Institute, 2023)
The fourth round of the Myanmar Household Welfare Survey (MHWS), a nationally and regionally representative phone survey, was implemented between October and December 2022. It follows from three rounds that were carried out quarterly beginning in December 2021. This report discusses the findings from the fourth round related to shocks, coping strategies, and income poverty. The security situation in Myanmar continued to deteriorate during the fourth-round recall period. Increasingly, households felt insecure in their communities, as reported by 22 percent of rural households and 27 percent of urban households, an increase compared to the previous rounds. This is because crime and violence continued to increase, affecting 12 and 8 percent of communities, respectively. Further, 8 percent of households were directly affected, either through violence against a household member, robbery, or appropriation and/or destruction of their assets. Households faced multiple disruptions besides insecurity. Disruptions in banking, internet, and electricity also negatively affected household wellbeing and livelihoods. Further, households struggled to receive medical services. Finally, while school attendance recovered, it was still under 70 percent in some states/regions. Eighty-four percent of households used at least one coping strategy to meet daily needs during the month prior to the fourth-round survey. The three most common coping strategies used were spending savings, reducing non-food expenditure, and reducing food expenditure. This has been consistent across rounds. Further, some households exhausted some or all of their coping strategies. Remittances were the only factor inversely associated with households’ probability of having lower income compared to last year, being income poor, and using coping strategies. In R4 income-based poverty increased by 30 percent compared to R1 (15 percentage points) and 7 percent compared to R3 (4 percentage points). Sixty-six percent of the population was income poor. The rise in income poverty between R3 and R4 was largely attributable to changes in urban poverty. Casual wage-earning households, both farm and non-farm, had the highest levels of income poverty. Compared to the other states/regions, households in Kayah, Chin, and Sagaing were the most vulnerable. They were more likely to be impacted by conflict, have income loss, and be income poor. Despite reporting comparatively less conflict, households in Rakhine were also vulnerable; nearly 80 percent of households in Rakhine were income poor and many were mortgaging/selling assets to cope.